2004
DOI: 10.1109/tns.2004.839174
|View full text |Cite
|
Sign up to set email alerts
|

Single event transient pulse widths in digital microcircuits

Abstract: The radiation effects community has long known that single event transients in digital microcircuits will have an increasing importance on error rates as device sizes shrink. However separating these errors from static errors in latch cells has often proved difficult. Thus determining both the significance and the nature of these transient errors has not been easy. In this study, by utilizing a latch that is radiation hard at static clock frequencies the errors due to transients could be separated. By separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(23 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…As expected, this also confirms that larger LETs result in larger pulse widths. It is interesting to note that the SET pulse widths predicted from these simulations are relatively smaller than observed for earlier technology nodes in [1][7] [9]. Although a direct comparison with transient current measurements reported in [8] cannot be made because of very large size devices under test and a different technology used in that work (50nm), our simulations agree with the trend that SET pulse widths are getting smaller in sub-100nm technologies.…”
Section: Set Pulse Widths For Large Letssupporting
confidence: 77%
See 1 more Smart Citation
“…As expected, this also confirms that larger LETs result in larger pulse widths. It is interesting to note that the SET pulse widths predicted from these simulations are relatively smaller than observed for earlier technology nodes in [1][7] [9]. Although a direct comparison with transient current measurements reported in [8] cannot be made because of very large size devices under test and a different technology used in that work (50nm), our simulations agree with the trend that SET pulse widths are getting smaller in sub-100nm technologies.…”
Section: Set Pulse Widths For Large Letssupporting
confidence: 77%
“…Numerous efforts have been made to indirectly characterize SETs through experimentation [1][7] [9]. A more recent effort by FerletCavrois et al [8] succeeded in measuring transient current pulses on relatively large devices in real-time conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent in-depth studies have concluded that SET pulses can be much larger than this. While particle strikes with linear energy transfer (LET) of 5-10 MeV-cm /mg often produce 100-200 ps pulses, cosmic ray strikes with LET of 100 MeV-cm /mg can induce SET pulses up to 2 ns long [12]- [14]. In general, SET pulse widths increase linearly with increasing LET from particle strikes [15].…”
Section: Schemes For Eliminating Transient-widthmentioning
confidence: 99%
“…Since drive strength is fixed for a given circuit, higher LETs will create a longer t SET . t SET has been shown to increase with decreasing process sizes [7][8] thus increasing the importance of SETs in ICs as technology processes progress.…”
Section: ) Single Event Transientsmentioning
confidence: 99%